Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1073/pnas.202260999
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of endothelial nitric oxide synthase with a voltage-dependent anion channel

Abstract: Endothelium-derived nitric oxide (NO) is an important regulator of vascular function. NO is produced by endothelial NO synthase (eNOS) whose function is modulated, in part, by specific protein interactions. By coimmunoprecipitation experiments followed by MS analyses, we identified a human voltage-dependent anion͞ cation channel or porin as a binding partner of eNOS. The interaction between porin and eNOS was demonstrated by coimmunoprecipitation studies in nontransfected human endothelial cells and Cos-7 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
1
53
0
2
Order By: Relevance
“…34,35 Immunoblotting was performed using monoclonal antibodies to eNOS (1:1000 dilution; Transduction Laboratories, Lexington, Ky), to p85 antiserum (1:500 dilution; Upstate Biotech), to phospho-eNOS (Ser1177), phospho-Akt (Ser473), and Akt (1:1000 dilution; Cell Signaling Tech), to hsp90 (1:200 dilution; Santa Cruz Biotech), and to ␣ -tubulin (DM1A) (1:5000 dilution; Sigma). Immunodetection was accomplished using a sheep anti-mouse secondary antibody (1:2000 dilution) or donkey anti-rabbit secondary antibody (1:2000 dilution) and the enhanced chemiluminescence (ECL) kit (Amersham Corp).…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…34,35 Immunoblotting was performed using monoclonal antibodies to eNOS (1:1000 dilution; Transduction Laboratories, Lexington, Ky), to p85 antiserum (1:500 dilution; Upstate Biotech), to phospho-eNOS (Ser1177), phospho-Akt (Ser473), and Akt (1:1000 dilution; Cell Signaling Tech), to hsp90 (1:200 dilution; Santa Cruz Biotech), and to ␣ -tubulin (DM1A) (1:5000 dilution; Sigma). Immunodetection was accomplished using a sheep anti-mouse secondary antibody (1:2000 dilution) or donkey anti-rabbit secondary antibody (1:2000 dilution) and the enhanced chemiluminescence (ECL) kit (Amersham Corp).…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…Furthermore, numerous groups have shown that CRP impairs endothelial vasoreactivity in vivo (11 ). To date, eNOS has been shown to interact directly with several proteins, including heat shock protein 90 (Hsp90), calmodulin, dynamin-2, caveolin-1, the intracellular domains of certain G protein-coupled receptors, and porin, a voltage-dependent anion/cation channel (5)(6)(7)(12)(13)(14)(15). The most important interactions for activity appear to relate to its association with caveolin-1 (decreased activity) and Hsp90 (increased activity) (5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…However, caveolin, which competes with and displaces calmodulin from eNOS, inhibits eNOS activity in the caveolae of endothelial cells and cardiomyocytes (10,11). Other eNOS interacting proteins such as heat shock protein 90 and a voltage-dependent anion/cation channel, porin, also regulate eNOS activation through protein stabilization, sub-cellular localization, and cofactor availability (12,13). Thus, proteins that interact with eNOS are important physiological regulators of eNOS activity.…”
mentioning
confidence: 99%